The simulation argument reconsidered. - Harris, Keith Raymond (Analysis, 2024)
Some philosophers regard it as a serious possibility that we now exist within a simulation. That this hypothesis is somewhat probable has been defended extensively by Nick Bostrom. Notably, Bostrom does not defend the conclusion that we inhabit a simulation, but rather the disjunctive conclusion that the human species is very likely to die out before reaching a 'posthuman stage', that posthuman civilizations are extremely unlikely to run significant numbers of simulations, or that we almost certainly inhabit a simulation. Bostrom argues that there is no basis for strongly favouring one of these alternatives over its counterparts. The upshot is that it is fairly probable that we inhabit a simulation. I argue that posthuman civilizations are likely to be unwilling to run significant numbers of simulations, thereby undermining the case for assigning a somewhat high probability to the hypothesis that we live in a simulation.